Hydrothermal in situ preparation of phthalocyanine-TiO2 nanocomposites for photocatalytic activity under visible light irradiation - Gorduk, Semih; Avciata, Oguzhan; Avciata, Ulvi (SPRINGER, 2021)
In this study, phthalocyanine (Pc)-TiO2 nanocomposites were prepared via in situ hydrothermal method. The metal-free, zinc(II), cobalt(II), nickel(II) and copper(II) Pc compounds were used for formation of nanocomposites. A total of 5 different Pc-TiO(2)nanocomposites was successfully prepared by hydrothermal method. The prepared nanocomposites were also characterized by FT-IR, XRD, FEG-SEM, EDX, UV-DRS and BET techniques. All prepared nanocomposites were tested for their photocatalytic activity to be used as photocatalyst. For this purpose, photocatalytic activities of Pc-TiO(2)nanocomposites were evaluated for the degradation efficiency of methylene blue (MB) under visible light irradiation by monitoring the UV-Vis absorption spectra. Based on the conducted studies, it was observed that Pc-TiO2 photocatalysts have significant photocatalytic activities on degradation of MB under visible light irradiation, resulting in complete degradation of MB in 100-130 min for full degradation (100%). Furthermore, the reusability studies revealed that photocatalysts show 76% activity even after 5 uses.
Keywords: TiO2; Hydrothermal; Photocatalytic activity; Phthalocyanine; Nanocomposite; ORGANIC POLLUTANTS; METHYLENE-BLUE; DEGRADATION; DYES; CONTAMINANTS; ZN(II); CO(II); ZN; Chemistry